‘UMUM AL-BALWA DALAM PERSPEKTIF HUKUM ISLAM - Mahmudin Mahmudin (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2020)
As a Muslim sometimes it is not always an easy thing to do with his worship, and it may be that the situation is outside of his widowed, for example, the many difficulties he faced, hard work and difficult to avoid it, there is an equitable and thorough incident or in the situation ‘umum al-balwa, Islam is the religion of shaalihun li kulli zaman wal makan (religion that always corresponds to the development of time and place) has a specific mechanism and principle in establishing the law and assessing every situation faced by a Muslim and all acts Horn in the exercise of worship to Allah SWT, Islam has also given a solution in every problem he faced for the benefit of human life in order to worship Allah SWT. Keywords: ‘Umum Balwa, Islamic law